Case Report: Bortezomib Plus CDOP Followed by Sequential Autologous Hematopoietic Stem Cell Transplantation and Lenalidomide-Based Maintenance Therapy in Plasmablastic Lymphoma - Cai, Jiao; Qiu, Ling; Ma, Lei; Zhang, Nan; Fan, Fang-yi (Frontiers in Medicine, 2021)
The standardized treatment plan on patients with plasmablastic lymphoma (PBL) remains controversial. Taking morphological characteristics and immunophenotype into consideration may provide superior options in the treatment of PBL. In this case, we report that myeloma-type regimen containing bortezomib plus CDOP followed with sequential ASCT and lenalidomide-based maintenance therapy to treat PBL may represent a promising regimen to improve the prognosis.